Mistreatment behaviours in the Athlete-coach relationship - Philippe Marracho; Eduarda Maria Rocha Teles de Castro Coelho; Antonino Manuel Almeida Pereira; Miguel Venda da Graça Nery (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This qualitative study aimed to describe the nature of mistreatment behaviours in the Athlete-coach relationship, in the region of Trás-os-Montes e Alto Douro, Portugal. For our study, we interviewed 12 athletes of federated sports. We focused on young athletes, aged 13-18 years old, who practiced a collective, combat, or individual sports discipline. The data was then studied through content analysis.